ELECTRONIC MAIL: A USEFUL COMMUNICATION TOOL FOR THE COLLEGE STUDENT - Krishnamurthi, Malini (Malaysian Journal of Library and Information Science, 1998)
Describes an exploratory survey of e-mail use pattern and attitudes towards e-mail among students at the California State University. On average students sent three and receives four messages per day. The results indicate that students felt that e-mail use was useful in the classroom to communicate with their instructors and classmates. They also felt that e-mail would be an appropriate medium to send brief messages and lengthy assignments. Students were comfortable with their keyboarding skills and were confident about using computers and found the system use-friendly. Ratings on computer anxiety was found to be positively correlated to e-mail use (r.=.47, p<.05) as well as system user-friendliness and e-mail use (r=.38, p<.05).